Potensi Pengembangan Ekowisata Berbasis Masyarakat di Kawasan Hutan Selelos Kabupaten Lombok Utara - R. Didi Kuswara; Nurmiati Nurmiati (Bioscientist : Jurnal Ilmiah Biologi, 2020)
The purpose of this study was to determine the potential of natural and cultural resources, to know the perceptions, participation and aspirations of the community and to develop a community-based ecotourism development strategy in Selelos Village, Gangga District, North Lombok Regency. This type of research is a descriptive qualitative case study and exploratory descriptive to find the potential in the form of biodiversity in the Selelos forest area. Data collection was carried out by observing the biodiversity in it, testing water quality, and using a questionnaire to 50 community respondents and 7 respondents from the village government. The results showed that Selelos Village has a forest area ecosystem that holds several potentials to be developed into ecotourism, including: waterfalls, springs, customary forests, and plantations (agro-tourism). In addition, it has a diversity of flora and fauna, there are about 13 high-level plant families with many species in it, as well as about 5 families of fauna and there are also endemic animals such as partridge and deer (senggah). Of the four springs quality tested, all of them are suitable as raw material for drinking water. Meanwhile, based on the questionnaire analysis, the community and village government will work together in developing and managing ecotourism. Based on the SWOT analysis, the strategy used in developing ecotourism is to take advantage of the strengths of opportunity (S-O), among others; mapping the potential of ecotourism, developing special ecotourism such as agro-tourism, synergizing ecotourism with local culture and customs, equipping, providing facilities and infrastructure, and improving human resources.